Characteristics of Patients With Aneurysmal Subarachnoid Hemorrhage and Risk Factors Related to Dysphagia - Rhie, Seung Hwa (Ann Rehabil Med, 2016)
OBJECTIVE: To investigate the characteristics and risk factors of dysphagia with the Videofluoroscopic Dysphagia Scale (VDS) using a videofluoroscopic swallowing study (VFSS) in patients with ruptured aneurysmal subarachnoid hemorrhage (aSAH). METHODS: Data of 64 patients presenting with first-ever ruptured aSAH were analyzed. Characteristics of dysphagia were evaluated using VFSS and all subjects were divided into a high (>47) and low risk group (≤47) by the VDS score. Clinical and functional parameters were assessed by medical records including demographics, hypertension and diabetes mellitus (DM), the Glasgow Coma Scale (GCS), the Hunt and Hess scale, endotracheal intubation, acute management modalities, as well as Korean version of the Mini-Mental Status Examination (K-MMSE) and Korean version of Modified Barthel Index (K-MBI). Radiologic factors identified the amount of hemorrhage, ventricular rupture, and aneurysmal location. RESULTS: About a half of the subjects showed oral phase abnormalities and the oral transit time was delayed in 46.8% of the patients. The pharyngeal transit time was also prolonged in 39.0% of the subjects and the proportion of penetration and aspiration observed was 46.8%. The parameters-GCS score (p=0.048), hemorrhagic volume (p=0.028), presence of intraventricular hemorrhage (p=0.038), and K-MMSE (p=0.007)-were predisposing factors for dysphagia in patients with aSAH. CONCLUSION: Abnormalities in the oral phase were more prominent in patients with aSAH than in those with other types of stroke. The risk factors associated with dysphagia persisting over 6 months after stroke onset were the initial GCS, hemorrhage volume, presence of intraventricular hemorrhage, and cognitive status as measured by the K-MMSE.